Gene Transfer to the CNS Using Recombinant Adeno‐Associated Virus. Issue 1 (1st May 2013) - Stoica, Lorelei; Ahmed, Seemin S.; Gao, Guangping; Sena‐Esteves, Miguel
Abstract: Recombinant adeno‐associated virus (rAAV) vectors are great tools for gene transfer due to their ability to mediate long‐term gene expression. rAAVs have been used successfully as gene transfer vehicles in multiple animal models of CNS disorders, and several clinical trials are currently underway. rAAV vectors have been used at various stages of development with no apparent toxicity. There are multiple ways of delivering AAV vectors to the mouse CNS, depending on the stage of development. In neonates, intravascular injections into the facial vein are often used. In adults, direct injections into target regions of the brain are achieved with great spatiotemporal control through stereotaxic surgeries. Recently, discoveries of new AAV vectors with the ability to cross the blood brain barrier have made it possible to target the adult CNS by intravascular injections. Curr. Protoc. Microbiol . 29:14D.5.1‐14D.5.18. © 2013 by John Wiley & Sons, Inc.